Identifying Protein Allosteric Transitions for Drug Discovery with 1D NMR. (12th April 2017) - Krimm, Isabelle
Abstract: Allosteric drugs present many advantages over orthosteric drugs and are therefore an attractive approach in drug discovery, despite being highly challenging. First, the binding of ligands in protein allosteric pockets do not ensure an allosteric effect, and second, allosteric ligands can possess diverse modes of pharmacology even within a compound family. Herein we report a new method to: 1) detect allosteric communication between protein binding sites, and 2) compare the effect of allosteric ligands on the allosteric transitions of the protein target. The method, illustrated with glycogen phosphorylase, consists of comparing 1D saturation transfer difference (STD) NMR spectra of a molecular spy (here fragments) in the absence and presence of allosteric ligands. The modification of the STD NMR spectrum of the fragment indicates whether the protein dynamics/conformations have been changed in the presence of the allosteric modulator, thereby highlighting allosteric coupling between the binding pocket of the reference compound (in this case the fragment) and the allosteric pocket. Abstract : The other site : Allosteric drug discovery is an attractive approach for the generation of drugs with improved safety, while being highly challenging. Fundamental issues are the identification of allosterically coupled protein pockets and the observation of the allosteric effect resulting from ligand binding. Herein we report a method for the detection and comparison of ligand‐induced allosteric transitions based on 1D NMR spectroscopy.